DNA extracted from saliva for methylation studies of psychiatric traits: Evidence tissue specificity and relatedness to brain. Issue 1 (29th October 2014) - Smith, Alicia K.; Kilaru, Varun; Klengel, Torsten; Mercer, Kristina B.; Bradley, Bekh; Conneely, Karen N.; Ressler, Kerry J.; Binder, Elisabeth B.
Abstract : DNA methylation has become increasingly recognized in the etiology of psychiatric disorders. Because brain tissue is not accessible in living humans, epigenetic studies are most often conducted in blood. Saliva is often collected for genotyping studies but is rarely used to examine DNA methylation because the proportion of epithelial cells and leukocytes varies extensively between individuals. The goal of this study was to evaluate whether saliva DNA is informative for studies of psychiatric disorders. DNA methylation (HumanMethylation450 BeadChip) was assessed in saliva and blood samples from 64 adult African Americans. Analyses were conducted using linear regression adjusted for appropriate covariates, including estimated cellular proportions. DNA methylation from brain tissues (cerebellum, frontal cortex, entorhinal cortex, and superior temporal gyrus) was obtained from a publically available dataset. Saliva and blood methylation was clearly distinguishable though there was positive correlation overall. There was little correlation in CpG sites within relevant candidate genes. Correlated CpG sites were more likely to occur in areas of low CpG density (i.e., CpG shores and open seas). There was more variability in CpG sites from saliva than blood, which may reflect its heterogeneity. Finally, DNA methylation in saliva appeared more similar to patterns from each of the brain regions examined overall than methylation in blood. Thus, this study provides a framework for using DNA methylation from saliva and suggests that DNA methylation of saliva may offer distinct opportunities for epidemiological and longitudinal studies of psychiatric traits. © 2014 Wiley Periodicals, Inc.